Comparison of Learning Achievement of Basic Mandarin by Using Storyline Instructional Model for the Third Graders, Kularbwittaya School - โลกานุวัตรเสถียร, วรรษมน (Academic Journal of MBU Lanna, 2020)
The purposes of this study was 1) compare learning achievement in communicative skills in Mandarin before and after the learning management using storyline method to improve communicative skills in mandarin of the third graders at Kularbwittaya School, and 2) to survey the attitude toward learning Mandarin of the third graders at Kularbwittaya School. The participants were 29 third graders at Kularbwittaya School, obtained by simple random sampling. The instruments included lesson plans based on storyline method, achievement test in Mandarin for the third graders, and a questionnaire surveying attitude toward learning Mandarin. Statistics used in this study were Mean, Standard Deviation, and t-test. The study indicated that 1) The participants’ scores of learning achievement in Mandarin after the learning management based on storyline method was significantly higher than the scores before the learning at the .05 statistical level, and 2) the participants had ‘good’ attitude toward learning Mandarin